Improved Representation of Underwater Light Field and Its Impact on Ecosystem Dynamics: A Study in the North Sea. Issue 7 (23rd July 2020) - Skákala, Jozef; Bruggeman, Jorn; Brewin, Robert J. W.; Ford, David A.; Ciavatta, Stefano
Abstract: Understanding ecosystem state on the North‐West European (NWE) Shelf is of major importance for both economy and climate research. The purpose of this work is to advance our modeling of in‐water optics on the NWE Shelf, with important implications for how we model primary productivity, as well as for assimilation of water‐leaving radiances. We implement a stand‐alone bio‐optical module into the existing coupled physical‐biogeochemical model configuration. The advantage of the bio‐optical module, when compared to the preexisting light scheme is that it resolves the underwater light spectrally and distinguishes between direct and diffuse downwelling streams. The changed underwater light compares better with both satellite and in situ observations. The module lowered the underwater photosynthetically active radiation, decreasing the simulated primary productivity, but overall, the improved underwater light had relatively limited impact on the phytoplankton seasonal dynamics. We showed that the model skill in representing phytoplankton seasonal cycle (e.g., phytoplankton bloom) can be substantially improved either by assimilation of satellite phytoplankton functional type (PFT) chlorophyll, or by assimilating a novel PFT absorption product. Assimilation of the two PFT products yields similar results, with an important difference in the PFT community structure. Both assimilative runs lead to lower plankton biomass and increase the nutrient concentrations. We discuss some future directions on how to improve our model skill in biogeochemistry without using assimilation, for example, by improving nutrient forcing, retuning the model parameters, and using the bio‐optical module to provide a two‐way physical‐biogeochemical coupling, improving the consistency between model physical and biogeochemical components. Key Points: We provided a state‐of‐the‐art marine ecosystem model with spectrally and directionally resolved incoming radiation We improve model skill to represent underwater light field in the North Sea With the help of assimilation, we also improve model skill to represent ecosystem dynamics